2009
DOI: 10.1007/s00253-008-1760-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial volatiles and their action potential

Abstract: During the past few years, an increasing awareness concerning the emission of an unexpected high number of bacterial volatiles has been registered. Humans sense, intensively and continuously, microbial volatiles that are released during food transformation and fermentation, e.g., the aroma of wine and cheese. Recent investigations have clearly demonstrated that bacteria also employ their volatiles during interactions with other organisms in order to influence populations and communities. This review summarizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
351
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 482 publications
(371 citation statements)
references
References 57 publications
6
351
1
2
Order By: Relevance
“…Along with plant roots, microorganisms have been reported to be a major source of VOCs produced in soils (Stotzky and Schenk 1976;Stahl and Parkin 1996;Mackie and Wheatley 1999;Isidorov and Jdanova 2002;Leff and Fierer 2008;Kai et al 2009;Insam and Seewald 2010). In contrast to this and despite microbial VOC production, plain soil (without plant roots) is reported to be a VOC sink, strongly dependent on soil temperature and moisture (Asensio et al 2007a).…”
Section: Microbial Growth and Voc Productionmentioning
confidence: 90%
“…Along with plant roots, microorganisms have been reported to be a major source of VOCs produced in soils (Stotzky and Schenk 1976;Stahl and Parkin 1996;Mackie and Wheatley 1999;Isidorov and Jdanova 2002;Leff and Fierer 2008;Kai et al 2009;Insam and Seewald 2010). In contrast to this and despite microbial VOC production, plain soil (without plant roots) is reported to be a VOC sink, strongly dependent on soil temperature and moisture (Asensio et al 2007a).…”
Section: Microbial Growth and Voc Productionmentioning
confidence: 90%
“…Currently, most studies on microbial volatiles are performed in vitro under nutrient rich conditions (Kai et al, 2009;Weise et al, 2012) and may not represent the conditions that prevail in the microbial environment. Furthermore, as indicated by Garbeva et al (2014a,b), the composition of volatiles produced by a mixture of bacterial species can differ from those produced by each bacterial monoculture.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to volatiles can strongly differ between fungal species and the extent of inhibition depends on the individual bacteria-fungus or fungus-fungus interaction (Kai et al, , 2009Vespermann et al, 2007;Garbeva et al, 2014b). Several independent studies have reported that F. solani is not much affected by bacterial volatiles, whereas Pythium species (oomycetes) are highly sensitive to bacterial volatiles (Kai et al, 2009;Effmert et al, 2012;Garbeva et al, 2014a,b).…”
Section: Volatile-mediated Antifungal Activitymentioning
confidence: 99%
See 2 more Smart Citations